Limitation of high-power optical radiation by organic molecules: I. Substituted pyranes and cyanine dyes - Kopylova, Tatyana N.; Svetlichnyi, Valerii A.; Mayer, Georgy V. 1948-; Reznichenko, A. V.; Podgaetskii, V. M.; Ponomareva, O. V.; Samsonova, Lyubov G.; Filinov, D. N.; Pomogaev, Vladimir A.; Telminov, Evgenii N.; Lapin, Ivan N.; Svetlichnaya, N. N.; et al. (Quantum electronics)
Photophysical processes proceeding in polyatomic organic molecules (pyran derivatives and cyanines) excited by high-power laser radiation at 532 nm are studied. Some properties of their changes depending on the structure, solvent, and excitation conditions are determined. The effect of limitation of high-power exciting radiation by the organic molecules is found. The maximum limitation (Kmax = 15.0 at the initial transmission equal to 70 %) was observed for the cyanine derivative and is comparable to this effect for fuUerenes C60, which are widely used as radiation limiters.